PENGARUH MODEL PEMBELAJARAN KOOPERATIF STAD BERBASIS MULTI MEDIA INTERAKTIF TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI TERMODINAMIKA - Jamuri -; Kosim -; Aris Doyan (Postgraduate, University of Mataram, 2015)
The objective of this study is : To know The influence of learning cooperative STAD model based on interactive multi media toward the student’s mastery concept of thermodynamics. Type of study done ,is experimental research by pretest-post test control group design. Population study is XI grade of Science students in SMAN 5 Mataram. The sample was chosen two classes which taken 73 students with random sampling which consisted of 37 students for experiment and 36 students for control. In this research taken through pretest and posttest by using the ability of problem solving student test toward experiment class and control class. The data analyzed by using N- gain to know the increase percentage of problem solving of student’s ability in each class. And ANAVA analysis to know cooperative learning model of STAD type based on interactive multi media toward the mastery of student concept in thermodynamics. Analysis result of N-gain shows that value reaches 70% with high category in mastery of student concept in experiment class. Whereas, the mastery of student concept in control class reaches 50% with average category. ANAVA analysis in significant level 5% shows significant score gotten 0,000 0,05 from significant level used. Based on the result of ANAVA analysis could be concluded that the use of cooperative learning model of STAD type based on interactive multimedia in learning thermodynamics influence toward the student’s mastery concept, Keywords: Learning Cooperative, Interactive Multi Media learning, Mastery Concept and problem solving ability